An enzyme-induced Au@Ag core–shell nanoStructure used for an ultrasensitive surface-enhanced Raman scattering immunoassay of cancer biomarkers. Issue 7 (3rd February 2017) - Yang, Lin; Gao, Ming Xuan; Zhan, Lei; Gong, Min; Zhen, Shu Jun; Huang, Cheng Zhi
Abstract : An ultrasensitive SERS immunoassay of AFP is developed by introducing an enzyme-induced deposition reaction to form a Au@Ag core–shell nanostructure. The limit of detection is 81 fg mL −1 . Abstract : Early detection of cancer is helpful for the control and prevention of diseases. Due to the low content of cancer biomarkers in the early disease phases, however, an ultrasensitive and selective method is critical. In this contribution, an ultrasensitive surface-enhanced Raman scattering (SERS) immunoassay is newly developed with the principle of introducing a common enzyme-induced deposition (EID) reaction to coat a silver layer on the surface of gold nanoparticles and to form a core–shell nanostructure of Au@Ag. By using alkaline phosphatase (ALP) to dephosphorylate its substrate, 2-phospho-l -ascorbic acid trisodium salt (AAP), to form vitamin C, silver ions could be reduced into silver atoms and coated on the surface of the AuNPs; a greatly enhanced SERS signal was then obtained. As a proof of concept, α-fetoprotein (AFP) was detected as a target, which is a biomarker of liver cancer. Excellent analytical performance of the SERS immunoassay could be achieved in the range from 0.5 to 100 pg mL −1 with a limit of detection of 0.081 pg mL −1 (3 σ ). Identical results could be obtained by using the newly proposed SERS immunoassay for the clinical detection of AFP in serum samples of patients to those clinically obtained by chemiluminescence immunoassays, demonstrating the potential applications of the developed method in clinical diagnosis.